A Comprehensive Overview of The Principles, Design, Operation, and Optimization of a Three-Bed TSA Dryer for Hydrogen Gas Dehydration - Islam, Md. Mirazul (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Dehydration of hydrogen gas is one of the important steps in many industrial purposes thus, drying systems have to be developed to achieve high efficiency and relative effect. In this article, the basic principles and design of a three-bed Temperature Swing Adsorption (TSA) dryer for dehydration operation of hydrogen gas drying are comprehensively described. The paper commences with an in-depth explanation of the basic principles behind TSA technology such as adsorption and desorption mechanisms, thermodynamic considerations and selection for adsorbents. This paper also deals with the detailed design of a three-bed TSA dryer, explaining about various fabricating details that influences both performance and overall operability. The third part focuses on the operational phase, and especially in cycle time, regeneration strategy and efficiency of energy. Advanced optimisation techniques are employed to lower energy consumption, increase throughput capacity and improve overall system performance. This detailed study will be of great help for engineers and investigators working on TSA systems design and optimization to dehydrate hydrogen gas, contributing towards the betterment in this important field dealing with industrial gas processing. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).